Study of Various Vesiculobullous Lesions Using Tzanck Smear - Singhal, Sanchit; M, Hemalata (Annals of Pathology and Laboratory Medicine, 2020)
Background: The vesiculobullous reaction pattern is characterized by the presence of vesicles or bullae within the epidermis or at the dermoepidermal junction. Despite some having characteristic presentations, it’s difficult to make a definite diagnosis clinically. Hence, cytological evaluation is required for reliable and early diagnosis. Objectives of the study are to determine the incidence of various vesiculobullous lesions and evaluate cytology as a tool for early diagnosis of vesiculobullous lesions. Methods: For Tzanck smears fresh vesicle or bulla was selected and incised with scalpel, reflecting the roof of bulla. Base of the blister scraped gently and material spread on a glass slide. These smears were stained with MGG (air dried), Pap and H&E stains (fixed).Skin punch biopsies from the bullae were subjected to routine fixation, processing, sectioning and staining. Results: A total of 62 Tzanck smears were done for vesiculobullous lesions of skin of which 29 had histopathological correlation. Herpes constituted the most common vesiculobullous disorder (42%) followed by bullous pemphigoid (27.4%) and pemphigus vulgaris (19.3%). Most patients were in the age group 61- 70 years. The M:F ratio of 1:1.38 showing female preponderance. Tzanck smears showed acantholytic cells in pemphigus group, eosinophils in bullous pemphigoid and multinucleate giant cells in viral blisters. Histopathology showed intraepidermal acantholysis in pemphigus vulgaris, subcorneal blister in pemphigus foliaceus and subepidermal in bullous pemphigoid. Conclusion: Cytohistopathological correlation showed an overall sensitivity of 79%. Tzanck smear showed 96% sensitivity for viral infections. Tzanck smear is a quick, non-invasive method for the early diagnosis of vesiculobullous disorders.